2009
DOI: 10.1021/ol901089h
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Doped Nanodiamonds: Synthesis and Functionalizations

Abstract: Oxadiamondoids representing a new class of carbon nanoparticles were prepared from the respective diamondoid ketones via an effective two-step procedure involving addition of methyl magnesium iodide and oxidation with trifluoroperacetic acid in trifluoroacetic acid. The reactivities of the oxacages are determined by the position of the dopant and are in good agreement with computational predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 30 publications
0
31
0
1
Order By: Relevance
“…Since the discovery of higher diamondoids in natural oil resources 11 several experimental [12][13][14][15][16] and theoretical studies 17,18 have revealed numerous unique and partly unanticipated properties. 20 A variety of diamondoids with different functional groups are now available [21][22][23][24] and further ways to modify diamondoid properties have recently been realized 25 or proposed. This development has gained momentum within the last few years due to the successful preparation of surface modified diamondoids.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of higher diamondoids in natural oil resources 11 several experimental [12][13][14][15][16] and theoretical studies 17,18 have revealed numerous unique and partly unanticipated properties. 20 A variety of diamondoids with different functional groups are now available [21][22][23][24] and further ways to modify diamondoid properties have recently been realized 25 or proposed. This development has gained momentum within the last few years due to the successful preparation of surface modified diamondoids.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the POLCYC computer program, 32 the IUPAC von Bayer nomenclature and carbon numbering were devised for all such zigzag catafusenes. 33 If the ends of an assembly similar to Figure 14 are connected into a cyclic structure, and if the dualist is now represented by olive-colored balls, the result is shown on the left part of Figure 15 as [26]cyclomantane in a ball-and-stick representation. On the right-hand side and without the dualist, the same [26]cyclomantane is shown in a representation with sticks for C-C bonds.…”
Section: Catafusene Structures Sharing One 6-membered Ring For Two Admentioning
confidence: 99%
“…Figure 15. Left: [26]cyclomantane with dualist, in ball and stick representation; right: the same, without dualist, in stick representation. …”
Section: Large-ring Perifusene Structuresmentioning
confidence: 99%
“…Thiole [13] (R-SH) für die Aufbringung auf Oberflächen, Amine [14] (R-NH 2 ) und Aminosäuren [15] (NH 2 -R-COOH) für medizinische Anwendungen oder in Halogene (F, Br) als Vorläufer für weitere Derivate umgewandelt werden. Außerdem ist es auch möglich, CH 2 -Gruppen aus dem Diamantoidkäfig gegen Sauerstoffatome auszutauschen und somit n-dotierte (elektronenreiche) nanoskalige Diamanten herzustellen [16]. Auf diesem Wege lassen sich kleinste organische Elektrobauteile mit den Eigenschaften des Diamanten durch selektives Heteroatomdoping herzustellen.…”
Section: Ursprung Der Diamantoideunclassified